ASSESSING THE SUBSTANTIVE EFFECTIVENESS OF ELECTRONIC MEDIATION IN DIVORCE CASES: AN EMPIRICAL STUDY AT THE SUNGGUMINASA RELIGIOUS COURT - Rezki Amalia (MADDIKA : Journal of Islamic Family Law, 2026)
The implementation of electronic mediation represents a strategic initiative by the Indonesian Supreme Court to modernize court-annexed dispute resolution through digital technology. However, the extent to which this innovation achieves the substantive objective of mediation, particularly in divorce cases, remains insufficiently understood. This study aims to analyze the effectiveness of electronic mediation in divorce cases at the Sungguminasa Religious Court Class 1A and identify the factors influencing its implementation and outcomes. Employing an empirical legal research design with a qualitative approach, the study collected data through in-depth interviews with 15 purposively selected informants, observations, and document analysis. Data were analyzed using Miles and Huberman’s, while the effectiveness of implementation was interpreted using Soerjono Soekanto's legal effectiveness theory. The findings reveal that the implementation of electronic mediation has complied procedurally with Supreme Court Regulation No. 3 of 2022 and is supported by adequate institutional facilities and digital infrastructure. Nevertheless, its substantive effectiveness remains limited. During the 2023–2025 period, 37 divorce cases were mediated electronically, of which 29 failed to reach a settlement, while only eight achieved partial agreements, primarily concerning ancillary issues rather than reconciliation. The limited effectiveness is predominantly attributable to prolonged marital conflicts, the parties' strong determination to divorce, lack of good faith to reconcile, constrained emotional interaction in virtual settings, and unequal levels of digital literacy, rather than technological shortcomings alone. These findings demonstrate that procedural compliance does not necessarily translate into substantive success. Accordingly, enhancing the effectiveness of electronic mediation requires strengthening mediators' virtual communication and psychological facilitation skills, improving public digital literacy, and developing mediation strategies that are more responsive to the characteristics of family disputes